PEMBERDAYAAN MASYARAKAT MELALUI KONVERSI LIMBAH SEKAM PADI MENJADI BIOCHAR DI DESA SIMPANG KUBU, KABUPATEN KAMPAR - Nursiani Lubis; Besri Nasrul; Sispa Pebrian; Denisa Sabrina; Gugun Paqta (LPPM Universitas Andalas, 2025)
Rice husk waste is a major by-product of rice milling that is abundant in agricultural areas such as Simpang Kubu Village, Kampar Regency, and is often burned or discarded, causing environmental pollution. This community service program aimed to enhance local knowledge, skills, and awareness in processing rice husk waste into biochar as an eco-friendly and economically valuable soil amendment. The activity was carried out in August–September 2025 using the Participatory Rural Appraisal (PRA) approach, involving 31 participants from farmer groups, housewives, and village officials. The methods included socialization, hands-on training in biochar production using a 208-liter rotary drum pyrolizer, and evaluation through pre- and post-tests. The results showed a significant increase in participants’ knowledge, from an average of 31% before training to 87.5% after training, with 92.9% expressing willingness to produce biochar and 100% interested in applying it to their farms. These findings indicate that an educational and participatory approach effectively improves community behavior and self-reliance in agricultural waste management. In conclusion, this program successfully strengthened community capacity to convert rice husk waste into useful products while promoting sustainable agriculture and rural economic development. The main challenges identified were limited production tools and participants’ confidence in assessing biochar quality; therefore, continued mentoring is needed to ensure independent and sustainable implementation of the technology.